A case of Gilbert’s syndrome diagnosis during pregnancy (Bangladesh Journal of Medical Science, 2020)
Gilbert’s syndrome (GS) is a benign condition that presents with recurrent jaundice due to isolated hyperbilirubinemia which predominates by its unconjugated component. It is a diagnosis of exclusion and often missed by attending physician. The uncertainty of diagnosis may cause anxiety among patients especially in pregnant women fearing the condition impacting the outcome of their pregnancies. We present a case of a primigravida woman with recurrent jaundice for the last ten years whohad not been givena definitive diagnosis of her illness despite on regular follow up in tertiary centre. She was anxious about her undiagnosed condition and the possibility of it affecting her pregnancy. Gilbert’s syndrome was diagnosed after evaluating information from the tertiary centre and she was assured regarding the prognosis of her pregnancy. She went into labour at term without complication and her postpartum period was uneventful.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.333-335